Examining Community Participation in the AMDAL Preparation Process Post-Job Creation Law Viewed from a Human Rights Perspective - Safitri, Nadila; Akbar, Sahda Saraswati; Nur Yacub, Tifanny (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
Since the publication of UU Cipta Kerja, the element of community involvement in the preparation of AMDAL, which is the guidance of corporations in managing the environment, has become narrower. This research aims to analyze the role of the community in preparing AMDAL after the enactment of UU Cipta Kerja and to analyze the environmental impact of companies on fulfilling community rights after the enactment of UU Cipta Kerja. This research uses normative juridical research methods and a statutory approach as well as a conceptual approach. The lack of community involvement in the preparation of AMDAL actually harms human rights because the Indonesian constitution and laws and regulations guarantee that everyone can express opinions, has the right to a healthy living environment, and has the right to be included in policy decision making. The enactment of UU Cipta Kerja itself resulted in a restructuring of AMDAL arrangements which made it easier for business actors and paid less attention to environmental policies and their impact on society.